Gene Expression Signatures of BRCAness and Tumor Inflammation Define Subgroups of Early-Stage Hormone Receptor-Positive Breast Cancer Patients - Schroth, Werner; Buettner, Florian A.; Kandabarau, Siarhei; Hoppe, Reiner; Fritz, Peter; Kumbrink, Joerg; Kirchner, Thomas; Brauer, Heather A.; Ren, Yuqi; Henderson, David; Madden, Stephen F.; Sauer, Georg; et al. (Clinical Cancer Research, 2020)
Purpose: Patients with estrogen receptor- and/or progesterone receptor-positive, early breast cancer benefit from hormonal treatment, yet high global death burdens due to high prevalence and long-term recurrence risk call for biomarkers to guide additional treatment approaches.
CRIS-Team WoS Importer:2021-02-05